Describing Sexting Pattern, Predictors, and Associated Risky Sexual Behaviors Among Post-Secondary School Young People in Ibadan, Nigeria (2020)
Sexting refers to sending and receiving sexually explicit (or suggestive) messages or videos. It has been described in different settings and among different populations mainly with a cross-sectional study design which is an important design that provides a base upon which other study designs can be built. However, it is important to pay close attention to some required details to obtain credible data which can produce useful results in cross-sectional study designs. This case write-up recounted how sexting was described among schooling young people in Nigeria. Particular attention was paid to the design of the data collection tool, selection of study participants, ethical considerations, and confidentiality as it relates to young people. It also described the different challenges that arose in the course of data collection and how these were handled with the resultant smooth research process.